Holographic inspired high-performance circular polarized spoof surface plasmon polariton leaky-wave antenna excited by a novel launcher - Sajjad Zohrevand; Mohammad Amin Chaychi Zadeh; Ehsan Farokhipour; Daniel Erni; Nader Komjani (Scientific Reports)
Abstract The holographic technique is one of the simplest methods for designing antennas based on metasurface. This paper presents a spoof surface plasmon polariton (SSPP) leaky-wave antenna (LWA) based on the concept of impedance modulated metasurfaces by the anisotropic holographic technique. Instead of parasitic elements, anisotropic SSPP elements are exploited to achieve radiation with circular polarization. The characteristics of the SSPP elements are obtained by the aperture field estimate method. The hologram surface consists of hollow cross-bars unit cells. The anisotropy of each unit cell is achieved by combining the transformation optic method and the particle swarm optimization algorithm. A major challenge of the SSPP LWA based on modulated impedance surfaces is to find a suitable excitation technique. This study proposes a waveguide strip line launcher for excitation to minimize interference on the radiation pattern beam. The designed launcher provides a good impedance matching from 8 to 20 GHz, with an impedance bandwidth of 142%. The peak gain, radiation efficiency, axial ratio (AR) bandwidth, and side lobe level at the design frequency of 18 GHz are 19.7dBi, 93%, 11%, and − 12.1 dB, respectively. After optimizations and simulations are conducted using MATLAB and CST software, the proposed antenna is fabricated, and its radiation characteristics are measured. The measured results agree well with the simulated ones, indicating the high validity of the method.